Taxonomic revision of the genus Penia Laporte (Coleoptera, Elateridae, Dendrometrinae) from Taiwan - Arimoto, Kôichi (Zootaxa, 2023)
The genus Penia Laporte, 1838 (tribe Dimini Candèze, 1863, subfamily Dendrometrinae Gistel, 1848) has three known endemic species from Taiwan. However, little is still known about these species and their important features, including genitalia. Here, the taxonomy of Taiwanese Penia is revised and eight species are confirmed: Penia alishanensis sp. nov., P. babai Kishii, 1994, P. elongata sp. nov., P. inopinata sp. nov., P. pulla sp. nov., P. smetanai Schimmel, 1996, P. takasago Kishii, 1997, and P. tsou sp. nov. The paratype of P. takasago is a different species and the species is described as P. inopinata. Three species have elongated bodies (P. alishanensis, P. elongata, and P. smetanai), whereas the other five have broad bodies. The eight species are distinguished from each other by the sizes of the eyes and apical maxillary palpomeres, the lengths of antennae and elytra, the relative length of the basal antennomeres, the degree of development of the mesosternal process between mesocoxae, and the shapes of the pronotum, hypomeron, scutellar shield and abdominal ventrite V. A key to all species in Taiwan is provided.